What stops Korean immigrants from accessing child and adolescent mental health services? - Chohye Park; Jik H. Loy; Steven Lillis; David B. Menkes (BMC, 2022)
Abstract Background Access to child and adolescent mental health services by ethnic minorities has been poorly studied. Despite rapid growth of the immigrant Korean population, evidence indicates that few Korean families utilise these services in New Zealand. Those that do tend to present late and with significant morbidity. We sought to understand barriers to service access from Korean parents' perspectives. Method Seven focus groups were undertaken with 31 Korean parents of children aged 18 and under. The focus groups were semi-structured, held in the Korean language and utilised two case scenarios of common childhood/adolescent mental illnesses around which a set of broad, open-ended questions were posed. All conversations were audiorecorded, transcribed and translated into English. Thematic analysis was conducted using NVivo software. Results Both attitudinal and structural barriers were identified. Attitudinal barriers included attribution of mental illness to external stressors or parenting problems, social stigma, denial or normalization of children's behaviour, fear of family disempowerment, and mistrust of public mental health services. Structural barriers included parents' lack of information regarding available services, logistical difficulties in access, communication difficulties, concerns over the quality of translators, and cultural competence of service providers. Conclusion Significant barriers prevent Korean immigrant families from accessing child and adolescent mental health services in New Zealand. Measures to improve access, for example by countering stigma, are urgently required.